Parent-Child Association of Sedentary Behavior According to Parental Physical Activity Level: The Epi-Family Health-Study - De Moraes-Ferrari, G (KeAi Communications Co., 2025)
The time spent in sedentary behavior (SB) has increased in children and adolescents, which may be positively associated with less time spent in physical activity and with an increase in health problems. Considering that the family environment can contribute to healthy and unhealthy habits, it is not known whether parental physical activity levels could mitigate the parent-child association of SB. Therefore, this study aimed to investigate the parent-child association of SB according to parental physical activity level. The sample consisted of children/adolescents (n ​= ​182) aged between 6 and 17 years (mean ± SD ​= ​[10.8 ​± ​3.4] years) and their parents [161 mothers (mean ± SD ​= ​[41.0 ​± ​5.5] years) and 136 fathers (mean ± SD ​= ​[43.6 ​± ​5.8] years)]. SB and physical activity were both measured with an accelerometer, and the parent-child association of SB was analyzed using Quantile Regression, adjusted by sex, age, socioeconomic status, and physical activity of the children/adolescents. An association of mother-child SB was observed in insufficiently active mothers (β ​= ​0.57; 95% CI ​= ​0.38; 0.75; p = 0.001), but not among mothers who were physically active (β ​= ​0.42; 95% CI ​= ​−0.05, 0.90; p = 0.081). When considering the father-child association of SB, a significant association was observed only among insufficiently active fathers (β ​= ​0.24; 95%CI ​= ​0.02, 0.45; p = 0.031), but not among fathers who were physically active (β ​= ​0.21; 95%CI ​= ​−0.16, 0.40; p = 0.403). These findings highlight the importance of encouraging PA in the family environment, in order to promote a reduction in SB and encourage physical activity engagement in the family environment. © 2025 Chengdu Sport University